Pembelajaran Inovatif Dalam Pengajaran Jarak Jauh Selama Pandemi Covid-19 - Dwiana Binti Yulianti (AL-ASASIYYA: Journal Of Basic Education, 2022)
This study aims to determine the description of distance teaching carried out by teachers/lecturers during the covid-19 pandemic. This study uses a library research method which is carried out by reading, studying, and also recording all information and literature related to the topic of discussion. The results show that the majority of teachers and lecturers use the Google Classroom and WhatsApp platforms for distance teaching. The use of these applications requires teachers/lecturers to prepare a practical and interesting learning framework for students. Remote teaching using Google classroom and Whats App is very effective and flexible. However, several obstacles were encountered when conducting distance teaching, including additional costs for providing internet quota, unstable networks that hindered the learning process, teachers/lecturers could not monitor students directly, resulting in a lack of interaction between teachers/lecturers and students, and online learning. only effective for theoretical subjects and very ineffective for practical subjects.